2020
DOI: 10.1093/aob/mcaa124
|View full text |Cite
|
Sign up to set email alerts
|

Corner’s rules pass the test of time: little effect of phenology on leaf–shoot and other scaling relationships

Abstract: Background and Aims The twig cross-sectional area and the surface area of leaves borne on it are expected to be isometrically correlated across species (Corner’s rules). However, how stable this relationship remains in time is not known. We studied the interspecific and intraspecific twig leaf area–cross-sectional area (la–cs) and other scaling relationships, including the leaf–shoot mass (lm–sm) scaling relationship, across a complete growing season. We also examined the influence of plant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…For trees, a shoot is a fundamental unit of growth ( Sterck et al , 2005 ; Sterck and Schieving, 2007 ; Lecigne et al , 2021 ) and reproduction ( Chen et al , 2009 ; Scott and Aarssen, 2013 ; Miranda et al , 2019 ; Fajardo et al , 2020 ). Given its importance, allometric relationships of shoot size and total shoot leaf area have been important topics in plant ecophysiology ( Corner, 1949 ; White, 1983 ; Ackerly and Donoghue, 1998 ; Brouat et al , 1998 ; Westoby and Wright, 2003 ; Kleiman and Aarssen, 2007 ; Olson et al ., 2009 , 2018 ; Sun et al ., 2010 , 2020 ; Yan et al , 2013 ; Trueba et al , 2016 ; Fan et al , 2017 ; Smith et al , 2017 ; Zhu et al , 2019 ; Fajardo et al , 2020 ). However, most previous studies on leaf vs. shoot size allometry have focused on the relationship among shoot size, total shoot leaf area, total leaf number and/or mean individual leaf size on the shoot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For trees, a shoot is a fundamental unit of growth ( Sterck et al , 2005 ; Sterck and Schieving, 2007 ; Lecigne et al , 2021 ) and reproduction ( Chen et al , 2009 ; Scott and Aarssen, 2013 ; Miranda et al , 2019 ; Fajardo et al , 2020 ). Given its importance, allometric relationships of shoot size and total shoot leaf area have been important topics in plant ecophysiology ( Corner, 1949 ; White, 1983 ; Ackerly and Donoghue, 1998 ; Brouat et al , 1998 ; Westoby and Wright, 2003 ; Kleiman and Aarssen, 2007 ; Olson et al ., 2009 , 2018 ; Sun et al ., 2010 , 2020 ; Yan et al , 2013 ; Trueba et al , 2016 ; Fan et al , 2017 ; Smith et al , 2017 ; Zhu et al , 2019 ; Fajardo et al , 2020 ). However, most previous studies on leaf vs. shoot size allometry have focused on the relationship among shoot size, total shoot leaf area, total leaf number and/or mean individual leaf size on the shoot.…”
Section: Introductionmentioning
confidence: 99%
“… Koyama et al , 2012 ; Smith et al , 2017 ), this fact was not considered in most previous studies on leaf size – shoot size allometry (e.g. Sun et al ., 2006 , 2010 , 2017 , 2019 a , b , 2020 ; Kleiman and Aarssen, 2007 ; Ogawa, 2008 ; Yang et al ., 2008 , 2009 , 2010 ; Milla, 2009 ; Xiang et al , 2009 a , 2010 ; Whitman and Aarssen, 2010 ; Dombroskie and Aarssen, 2012 ; Scott and Aarssen, 2012 , 2013 ; Yan et al , 2013 ; Dombroskie et al , 2016 ; Trueba et al , 2016 ; Olson et al , 2018 ; Miranda et al , 2019 ; Zhu et al , 2019 ; Fajardo et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Knowing that WD negatively relates to MVD across the wateravailability gradient, we consequently expected an also negative , 1998;Fajardo, Mora, et al, 2020;Olson et al, 2018). With this in mind, several previous studies found a negative relationship between WD and LA when hundreds of species were compared (Baraloto et al, 2010;Wright et al, 2007).…”
Section: Wood Density Growth and Leaf Traitsmentioning
confidence: 81%
“…Similarly, we can appeal to Corner's rules regarding leaf–shoot allometric scaling relationships to explain this negative WD‐MVD relationship. Corner's rules state that plants with large leaves tend to have thick twigs that branch sparingly, with wide piths, thick bark, low‐density, and flexible wood and bark; the opposite is true of plants with small leaves, which have slender twigs that branch intricately, with narrow piths, thin bark, and high‐density, stiff wood and bark (Ackerly & Donoghue, 1998; Fajardo, Mora, et al, 2020; Olson et al, 2018). With this in mind, several previous studies found a negative relationship between WD and LA when hundreds of species were compared (Baraloto et al, 2010; Wright et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Due to hydraulic and biomechanical selective pressures coupled with leaf attachment requirements, small twigs cannot support large leaves (Shinozaki, 1964;Westoby et al, 2002). The observation that twig diameter increases with leaf size, referred to as Corner's rule of axial conformity (Corner, 1949), is well supported by data (White, 1983;Ackerly and Donoghue, 1998;Brouat et al, 1998;Cornelissen, 1999;Westoby and Wright, 2003;Fajardo et al, 2020). We investigated whether plants economize on these investments by constructing large-diameter twigs with thick cores of pith, a low density, and low cost tissue.…”
mentioning
confidence: 99%